Pengaruh Risiko Sistematik, Leverage Dan Persistensi Laba Terhadap Earnings Response Coefficient (ERC) - Maisil Delvira; Nelvirita Nelvirita (Wahana Riset Akuntansi, 2013)
The objective of this research is to investigate (1) the effect of systematic risk on earnings response coefficient (ERC), (2) the effect of leverage on earnings response coefficient (ERC), and (3) the effect of earnings persistence on earnings response coefficient (ERC). Using manufacturing companies that listed in Indonesian Stock Exchange (IDX) from 2008 to 2010, we use purposive sampling, and get 43 manufacturing company.We find that : (1) systematic risk negatively affect earnings response coefficient (ERC), (2) leverage does not affect earnings response coefficient (ERC), and (3) earning persistence positively affect earnings response coefficient (ERC).   Keywords : earnings response coefficient (ERC), systematic risk, leverage,earnings persistence.